Ideas of Salvation - Adeyemo, Tokunboh (Africa Journal of Evangelical Theology, 1997)
The book by Dr Tokunboh Adeyemo, Salvation in African Tradition, was first published by Evangel Publishing House in 1979 and has been widely read in theological circles throughout Africa. In a recently revised edition in 1997 under the same title and also published by Evangel Publishing House, several additional chapters have been added. "Ideas of Salvation" is one additional chapter. In this chapter Dr Adeyemo outlines the various approaches to salvation found in world religions, including African Traditional Religion and the Christian faith.
Free
Keywords: Salvation – Comparative studies